2020
DOI: 10.1096/fj.201902055r
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 confers protection against diabetic coronary atherosclerosis by stimulating M2 macrophage polarization via the activation of the CREB/BDNF/TrkB signaling pathway

Abstract: It has been documented that M2 macrophage polarization plays a suppressive role in atherosclerosis in diabetes mellitus (DM). In addition, prostaglandin E2 (PGE2) is implicated in the development of M2 macrophage polarization. Therefore, the study aimed to investigate the specific mechanism of PGE2 in M2 macrophage polarization in diabetic coronary atherosclerosis (DMAS). Initially, clinical samples were obtained and DMAS mouse model was established. The expression of BDNF was determined, and M1 and M2 macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Some evidences describe that atherosclerotic progression is regulated by recruitment of macrophages, reflected in increased lipid accumulation, and thickened arterial wall 31 . Previous studies showed that blocking macrophage polarization toward an M1 status likely reduced atherosclerotic plaque burden and intimal area in atherosclerosis, 24 whereas the stimulation of M2 macrophage polarization protected against atherosclerotic lesions 32 . In the present study, we observed that HOXA5 inhibited neointimal hyperplasia and plaque formation in CAS mice.…”
Section: Discussionsupporting
confidence: 63%
“…Some evidences describe that atherosclerotic progression is regulated by recruitment of macrophages, reflected in increased lipid accumulation, and thickened arterial wall 31 . Previous studies showed that blocking macrophage polarization toward an M1 status likely reduced atherosclerotic plaque burden and intimal area in atherosclerosis, 24 whereas the stimulation of M2 macrophage polarization protected against atherosclerotic lesions 32 . In the present study, we observed that HOXA5 inhibited neointimal hyperplasia and plaque formation in CAS mice.…”
Section: Discussionsupporting
confidence: 63%
“…However, PGE 2 has also been linked with beneficial effects on the islet phenotype. For example, PGE 2 promotes M2 macrophage polarization, preventing pro-inflammatory cytokine production and promoting β-cell survival [5]. Therefore, what physiological changes might transition islet EP3 signaling from protective to detrimental remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is known to underlie the protective effect of PGE 2 against atherosclerosis. Bi et al (2020) have demonstrated that PGE 2 ameliorates diabetes-related atherosclerosis through the stimulation of macrophage polarization through the activation of the transcription factor Kruppel-like factor 4 (KLF4). Consistent with this finding, the pro-atherogenic effect of the COX-2 inhibitor celecoxib was recently associated with its suppressive effect on PGE 2 and NO levels, concomitantly with the induction of LTB 4 and LTs (Pang et al, 2019).…”
Section: Prostanoids From Aamentioning
confidence: 99%